ChemInform Abstract: (.+‐.)‐Paeoveitol, a Pair of New Norditerpene Enantiomers from Paeonia veitchii. Issue 26 (1st July 2014) - Chen, Ji‐Jun; et al., et al.
Abstract (.+‐.)‐Paeoveitol is isolated and resolved by chiral HPLC.